2006
DOI: 10.1007/s00330-005-0042-z
|View full text |Cite
|
Sign up to set email alerts
|

Can 16-detector multislice CT exclude skeletal lesions during tumour staging? Implications for the cancer patient

Abstract: Current imaging guidelines recommend that many cancer patients undergo soft-tissue staging by computed tomography (CT) whilst the bones are imaged by skeletal scintigraphy (bone scan). New CT technology has now made it feasible, for the first time, to perform a detailed whole-body skeletal CT. This advancement could save patients from having to undergo duplicate investigations. Forty-three patients with known malignancy were investigated for bone metastasis using skeletal scintigraphy and 16-detector multislic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
16
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 13 publications
2
16
0
5
Order By: Relevance
“…Recently, multislice CT has been proposed as an alternative to bone scintigraphy for whole-body screening of the skeletal system. Groves et al (39) found equivalence between scintigraphy and CT in detecting bone metastases. They suggested that patients undergoing whole-body staging with CT may not need the additional skeletal scintigraphy and consequently have a shorter diagnostic pathway (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, multislice CT has been proposed as an alternative to bone scintigraphy for whole-body screening of the skeletal system. Groves et al (39) found equivalence between scintigraphy and CT in detecting bone metastases. They suggested that patients undergoing whole-body staging with CT may not need the additional skeletal scintigraphy and consequently have a shorter diagnostic pathway (39).…”
Section: Discussionmentioning
confidence: 99%
“…Groves et al (39) found equivalence between scintigraphy and CT in detecting bone metastases. They suggested that patients undergoing whole-body staging with CT may not need the additional skeletal scintigraphy and consequently have a shorter diagnostic pathway (39). However, another recent study comparing multislice CT with MRI in the detection of metastases to the spine found that the sensitivity of MRI (98.5%) was considerably greater than that of CT (66%),with equivalent specificities (40).…”
Section: Discussionmentioning
confidence: 99%
“…This is also true for bone metastases if the chest, abdomen and pelvis are examined at the same time [22,23,24]. The 13 patients in our study with osseous metastases had at least 1 metastasis in an area (thorax, abdomen, pelvis) that would have been detected by means of CT [3].…”
Section: Discussionmentioning
confidence: 99%
“…Although CT as well as BS could detect bone metastases, our results indicate the superiority of BS over CT in terms of monitoring response in patients under treatment with ZA 38) . In cases of bone -only metastatic patients with normal ranges of TM, BS may therefore be the only reliable tool for monitoring responses to therapy.…”
Section: Discussionmentioning
confidence: 68%